Islamic Microfinance and Sustainable Development Goals in Bangladesh - Rashid, Md. Harun Ur; Uddin, Mohammed Jashim; Mohd. Zobair, Shah Asadullah (International Journal of Islamic Business & Management, 2018)
The main objective of this study is to explore the Islamic Microfinance Instruments in achieving the Sustainable Development Goals (SDGs) in Bangladesh. The methodology of this study is based on secondary data including existing relevant literature, and annual reports of different financial institutions. The findings of this study show that Islamic microfinance institutions have a broader scope to attain SDGs through their various investment modes.The study categorizes the Islamic microfinance instruments into four broadly parts which are profit and loss sharing financing, non-profit & loss sharing financing, Islamic social enterprise based financing and charity based financing which have a positive effect to the real sector of the sustainable economy that will lead towards achieving SDGs. The Islamic Microfinance institutions are continuing their efforts in attaining SDGs through their various products. With growing the potentiality, Islamic microfinance has both direct and indirect impacts on ensuring economic development, environmental sustainability, and social inclusion by creating employment opportunity, spreading knowledge and skills, making self-dependent, protecting from adverse effects. The paper also tries to put recommendations to reduce the challenges of Islamic microfinance acting as impediments to achieving the SDGs.